Growth of seedlings of Tabebuia rosea and Gliricidia sepium under hydrochloric salinity conditions - Sánchez-Bernal, Edgar Iván; Ortega-Escobar, Héctor Manuel; Muñoz-Hernández, Erika Nachele; Can-Chulim, Álvaro; Ortega-Baranda, Verónica; Ochoa-Somuano, Jorge (REVISTA TERRA LATINOAMERICANA, 2020)
A greenhouse experiment was conducted with agrolite pots, irrigated with sodium chloride (NaCl) solutions at concentrations of 0, 1.28, 2.56, 3.84, 5.12, 6.40 and 7.68 g L-1. The objective of our study was to evaluate emergence, height, stem diameter, length of the root, number of leaves and accumulation of total biomass of seedlings of Tabebuia rosea and Gliricidia sepium from the low deciduous forest of Oaxaca, and to determine their tolerance to salt. Results indicate that the increase of saline level delayed emergence and decreased growth of both plant species. The control plants were significantly larger than those grown in the saline treatments (P = 0.05). The growth reduction was differential, since concentrations > 6.40 g L-1 inhibited the emergence of Tabebuia rosea seedlings, whereas concentrations > 5.12 g L-1 produced dwarf ism in the seedlings of Gliricidia sepium. Salinities > 1.28 g L-1 produced burning of plant tissues and toxicity. In conclusion, Tabebuia rosea is less tolerant to hydrochloric salinity than Gliricidia sepium. The proposed regression model was consistent with the saline effect on decreasing the total dry weight of plants.